Calcium-mediated gelation of an olive pomace pectic extract - Cardoso, Susana M. (2003)
Pectic raw material was extracted from the alcohol insoluble residue of olive pomace. After purification, the olive pectic extract (OPE) contained 48% of galacturonic acid (GalA) and 31% of arabinose, in a total sugar content of 72%, and a degree of methylesterification (DM) of 43%. Phase diagrams were established to define the physical state of the OPE/calcium, systems, at pH 3 and 7, as a function of GalA and calcium concentration. The theological properties of the OPE/calcium systems were investigated by small-amplitude oscillatory tests. Kinetics of gel ageing and the viscoelastic properties of the cured gels were evaluated as a function of GalA and calcium concentration at pH 3 and 7. Compared with the observed behaviour of a citrus pectin, taken as representative of a commercial low-methoxyl pectin, the OPE showed higher critical GalA and calcium concentrations for gelation to occur, a larger region corresponding to homogeneous gel, and gels characterised by lower viscoelastic moduli, at similar GalA and calcium concentrations.